(untitled) (Medicine Today, 2026)
The health sector budget in Bangladesh has experienced significant growth over the past decade, reflecting the government’s increasing commitment to improving public health and healthcare infrastructure. This study explores the trends and implications of the health sector’s budget allocations from 2015 to 2025, with a focus on fiscal policies, government priorities, and the impact on public health outcomes. Using a longitudinal analysis of national budget documents and supplementary data from the Ministry of Health and Family Welfare, this report examines the correlation between budget increases and improvements in healthcare accessibility, quality of services, and health outcomes. The analysis reveals a consistent rise in the budgetary allocation, with notable jumps in the years 2017, 2020, and 2024. Despite these increases, the report highlights the challenges of translating budgetary growth into sustainable improvements due to systemic inefficiencies, underfunding of key areas, and a growing population. Recommendations include optimizing resource allocation, enhancing the efficiency of healthcare expenditure, and fostering greater public-private partnerships to ensure equitable access to healthcare services across Bangladesh. The report concludes that while budget growth is promising, targeted reforms and strategic investments are essential to achieve long-term health sector sustainability. Medicine Today 2026, Vol.38 (1): 142-147